114 Clinical, physical, cognitive and social frailty in patients with chronic heart failure: prevalence and associations with outcome. (4th June 2021) - Sze, Shirley; Pellicori, Pierpaolo; Zhang, Jufen; Weston, Joan; Squire, Iain; Clark, Andrew
Abstract : Background: Recently, the American College of Cardiology (ACC) and the Heart Failure Association (HFA) of the European Society of Cardiology (ESC) proposed a four-domain approach to assess frailty in patients with heart failure (HF), to tailor treatment and potentially improve outcomes.Aim: To study the prevalence and prognostic value of four different types of frailty deficits: clinical, physical, cognitive and social frailty in ambulatory patients with HF. Methods: We assessed prospectively consecutive patients attending a routine follow-up visit. Patients with ≥5 non-HF comorbidities were classified as having a clinical deficit. Those who scored ≥ 3 using the Fried criteria were classified as having a physical deficit. Those who failed to complete a clock test accurately were classified as having a cognitive deficit. Those who lived alone or in a residential home were classified as having a social deficit. Results: 467 patients (67% male, median (25th-75th centile) age 76 (69-82) years, median (25th-75th centile) NT-proBNP 1156 (469-2463) ng/L) were enrolled. 65% of patients had clinical deficits, 52% had a physical deficit, 39% had a social deficit and 18% had a cognitive deficit. 28% had 2, 19% had 3, 8% of patients had all 4 deficits; 16% had none. ( Figure 1 ). During a median follow-up of 554 days, 82 patients died. The presence of any frailty deficit was associated with increased risk of mortality. ( Figure 2 ) Patients with all 4 frailty deficits have a 15-fold increased risk of mortality compared to patients with no frailty deficit. A base model (including age, body mass index, NYHA class and log [NT-proBNP]) for predicting mortality at 1 year achieved a C-statistic of 0.78. Addition of all four deficits improved the performance of the base model (C-statistic = 0.82). Conclusion: Clinical, physical, cognitive and social deficits are common in patients with HF and are associated with a poor outcome. Future studies should evaluate how to optimise care for frail patients with HF using a domain management model. Conflict of Interest: none